1996
DOI: 10.1002/(sici)1096-9861(19960916)373:2<220::aid-cne5>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Widespread distribution of histamine in the nervous system of a trematode flatworm

Abstract: In general, most flatworms contain very little histamine (HA) and their nervous systems often lack, or contain very few, histaminergic elements. However, preliminary studies in our laboratory have revealed that the frog lung parasite, Haplometra cylindracea (Trematoda: Digenea), contains HA in a very high concentration. For this reason, the present study was undertaken to study the localization and synthesis of HA in this worm by using immunocytochemistry and high-pressure liquid chromatography (HPLC). Essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Since this time its advantageous effect was supported by a lot of experiments, e.g. in Planarians (Panula et al, 1995), Trematodes (Eriksson et al, 1996), zebrafish (Eriksson et al, 1998) and immune cells of the rat (Csaba et al, , 2004. The present results justify its superiority in the case of Tetrahymena as significantly more hormones were demonstrable in the EDAC-fixed preparations ( Table 1).…”
Section: Resultssupporting
confidence: 68%
“…Since this time its advantageous effect was supported by a lot of experiments, e.g. in Planarians (Panula et al, 1995), Trematodes (Eriksson et al, 1996), zebrafish (Eriksson et al, 1998) and immune cells of the rat (Csaba et al, , 2004. The present results justify its superiority in the case of Tetrahymena as significantly more hormones were demonstrable in the EDAC-fixed preparations ( Table 1).…”
Section: Resultssupporting
confidence: 68%
“…Collectively the dorsal neurogenic domains encompass the cells that comprise the larval apical organ noted for numerous sensory neurons and deeper supportive epithelial cells, many of which express histamine [39]. Widespread distribution of histamine within the sensory cells (photoreceptors and statocysts) and peripheral nervous systems of a trematode flatworm, some mollusks, and arthropods is well documented [50-53], and collectively support a role for histamine as a modulator of muscular contractions and ciliary beat during locomotive behaviors. Altenburger et al [38] found eight serotonergic sensory neurons in the larval apical organ of T. transversa that generally match the position and morphology of the central sensory neurons we labeled with the antibody against acetylated α-tubulin.…”
Section: Discussionmentioning
confidence: 99%
“…There is indirect evidence to indicate HA may serve as a neurotransmitter in arthropods and molluscs, but with two notable exceptions (Mesocoelium monodi, Haplometra cylindracea, see below), evidence of HA and/or its synthesis in flatworms is either poor or non-existent (Mettrick & Telford, 1963;Eriksson et al 1996); analysis of HA levels in Hymenolepis diminuta showed the worm does not synthesise the monoamine but likely acquires it from its host by diffusion (Yonge & Webb, 1992). Small numbers of histaminergic fibres have been demonstrated immunocytochemically in the turbellarians, Microstomum lineare and Polycelis nigra, and in the cestode, Diphyllobothrium dendriticum, where they are scattered mainly in the longitudinal nerve cords (Wikgren et al 1990).…”
Section: Histaminementioning
confidence: 99%
“…In contrast, extensive immunostaining for HA has been shown throughout the nervous system of the blood-feeding frog-lung trematode, Haplometra cylindracea and which, remarkably, has been found to contain one of the highest concentrations of HA in the animal kingdom, measuring 6-49+1-36 nmole/mg protein, a figure surpassed only by levels found in the mammalian gastric mucosa. Negligible amounts of HA were found in the host-frog lung and blood, and an enzyme assay by Eriksson et al (1996) showed the worm is capable of producing endogenous HA by decarboxylation of histidine. These findings, and the fact that another amphibian trematode, Mesocoelium monodi, contains quite high levels of HA (520 pmole/mg wet weight) and exhibits a high rate of HA synthesis (Mettrick & Telford, 1963), has prompted Eriksson et al (1996) to suggest that a well-developed histaminergic nervous system could advantage a parasite of amphibians, in that the latter produce insufficient exogenous HA to interfere with neural function in the flatworm.…”
Section: Histaminementioning
confidence: 99%